2004
DOI: 10.1016/j.ymthe.2003.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Striatal Delivery of rAAV-hAADC to Rats with Preexisting Immunity to AAV

Abstract: We tested the hypotheses that initial immunization of rats with rAAV might limit subsequent transduction by rAAV-hAADC when stereotaxically infused into the striatum and that the level of inhibition would correlate with AAV neutralizing antibody titers. Immunohistochemical detection of AADC and analysis by stereology revealed that the control group (no immunization) had the greatest volume of distribution of AADC (20.32 +/- 2.03 mm3) (+/-SD). There was a 58% decrease in spread (8.46 +/- 3.67 mm3, P < 0.008) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
66
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(70 citation statements)
references
References 27 publications
4
66
0
Order By: Relevance
“…[8][9][10][11][12][13][14][15][16][17][18][19] The existence of NAbs can limit rAAV therapeutic applications that rely on systemic vector administration, for example, by interfering with cell surface binding or promoting reticuloendothelial clearance and destruction of AAV vectors. [20][21][22] Additionally, previous human studies have observed that NAbs against AAV2 cross-neutralize other serotypes of AAV. 15 This problem is particularly relevant for patients with hemophilia because the most promising treatment relies on vector delivery to the liver through blood circulation.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11][12][13][14][15][16][17][18][19] The existence of NAbs can limit rAAV therapeutic applications that rely on systemic vector administration, for example, by interfering with cell surface binding or promoting reticuloendothelial clearance and destruction of AAV vectors. [20][21][22] Additionally, previous human studies have observed that NAbs against AAV2 cross-neutralize other serotypes of AAV. 15 This problem is particularly relevant for patients with hemophilia because the most promising treatment relies on vector delivery to the liver through blood circulation.…”
Section: Introductionmentioning
confidence: 99%
“…Dramatic inhibition of AAV vector gene delivery by NAb's has been demonstrated in numerous animal studies (Halbert et al, , 2000Hildinger et al, 2001;Manning et al, 1998). For example, Mandel et al (Peden et al, 2004) and Sanftner et al (2004) recently reported that pre-existing humoral immunity results in a moderate to significant loss in transduction efficiency even in the brain, considered an immune privileged tissue.…”
Section: Introductionmentioning
confidence: 99%
“…The potential utility of AAV-2 vectors for treating serious human diseases including hemophilia A and B (8), Parkinson's disease (1,19,31), heart failure (9, 21), and cystic fibrosis (14), among others, has been established in animal models. However, the presence of human preexisting antibodies reactive with primate AAV serotypes may reduce the clinical usefulness of vectors made from these serotypes (17).…”
mentioning
confidence: 99%